MENINGKATKAN KEMAMPUAN SISWA MEMBUAT KARYA SENI KOLASE MELALUI MODEL SNOWBALL THROWING DI KELAS IV - Fadilla, Dwi Badriyatul; Pulukadang, Wiwy Triyanty; Katili, Sukri; Pulukadang, Mimy Astuty; Husain, Rusmin (LEARNING : Jurnal Inovasi Penelitian Pendidikan dan Pembelajaran, 2025)
This study aims to improve students' abilities through making collage artwork using the snowball throwing model in class IV SDN 8 Kabila, Bone Bolango Regency. The method used in this study is Classroom Action Research (CAR) using data collection techniques, namely interviews, observations, tests and documentation with the research subjects of class IV students totaling 15 people at SDN 8 Kabila, Bone Bolango Regency. Based on the results of the study, data on student learning outcomes were obtained in cycle I, meeting I, from the total of 11 students present, it was seen that no students had achieved a creative assessment with a percentage of 0%. In cycle I, meeting II, from the total of 15 students present, it was seen that 4 students had achieved a creative assessment with a percentage of 27%. While in cycle II, from the total of 15 students present, it was seen that 14 students had achieved a creative assessment with a percentage of 93%. Thus, the indicator of the success of the action that had been set in this study had been met, namely 75%. The conclusion of this study is that making collage artwork using the snowball throwing model can help improve students' abilities in class IV SDN 8 Kabila, Bone Bolango Regency. ABSTRAKPenelitian ini bertujuan untuk meningkatkan kemampuan siswa melalui pembuatan karya seni kolase menggunakan model snowball throwing di kelas IV SDN 8 Kabila Kabupaten Bone Bolango. Metode yang digunakan dalam penelitian ini adalah Penelitian Tindakan Kelas (PTK) dengan menggunakan teknik pengumpulan data yaitu wawancara, observasi, tes dan dokumentasi dengan subjek penelitian siswa kelas IV yang berjumlah 15 orang di SDN 8 Kabila Kabupaten Bone Bolango. Berdasarkan hasil penelitian diperoleh data hasil belajar siswa pada siklus I pertemuan I dari jumlah 11 siswa yang hadir, terlihat belum ada siswa yang sudah mencapai penilaian kreatif dengan persentase 0%. Pada siklus I pertemuan II dari jumlah 15 siswa hadir, terlihat siswa yang sudah mencapai penilaian kreatif sebanyak 4 orang dengan persentase 27%. Sedangkan pada siklus II dari jumlah 15 siswa yang hadir, terlihat siswa sudah mencapai penilaian kreatif sebanyak 14 orang dengan persentase 93%. Dengan demikian indikator keberhasilan tindakan yang telah ditetapkan pada penelitian ini telah terpenuhi yaitu 75%. Kesimpulan dari penelitian ini adalah membuat karya seni kolase menggunakan model snowball throwing dapat membantu meningkatkan kemampuan siswa di kelas IV SDN 8 Kabila Kabupaten Bone Bolango.